Associations between partial foot amputation level, gait parameters, and minimum impairment criteria in para-sport: A research study protocol - de Oliveira, F. C. L.; Williamson, S.; Ardern, C. L.; Heron, N.; van Rensburg, D. C. J.; Jansen, M. G. T.; O'Connor, S.; Schoonmade, L.; Thornton, J.; Pluim, B. M. (Sports Medicine and Health Science, 2022)
Altered biomechanics due to amputation can contribute to substantial limitations, influencing sporting activities. Individuals with lower extremity amputations or congenital lower limb deficiency are encouraged to participate in para-sports. However, to compete in Paralympic sports, the candidate must have an impairment that results in lower extremity loss of function and meets or exceeds the sport's minimum impairment criteria (MIC). This review will focus on the MIC for competitive wheelchair tennis. Limb deficiency is known as one of the MIC used to regulate participation in competitive para-sports since it impacts gait, kinematics, and biomechanics of both the upper and lower body. Notwithstanding, it is questionable whether the MIC concerning limb deficiency is set at the correct level for determining eligibility for participating in Paralympic sports. This study aims to provide an overview of the evidence examining the impact of different partial foot amputation (PFA) levels on gait as a proxy for sporting performance. This scoping review will be based on a 6-step methodological framework and Preferred Reporting Items for Systematic Reviews and Meta-Analysis, extension for scoping reviews (PRISMA-ScR). Studies will be selected from PubMed, Embase, CINAHL, and SPORTDiscus. Two authors will screen the titles/abstracts independently. Selected studies will be scrutinised, and the same authors will extract data. Findings will be relevant to informing the evidence-based development of MIC for lower limb impairment after PFA and may be extrapolated to specific Paralympic sports, including wheelchair tennis. Results will be disseminated through scientific publications and conferences to audiences interested in Paralympic sports.